2012
DOI: 10.4330/wjc.v4.i6.206
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction: Clinical features and outcomes in young adults in Singapore

Abstract: AIM:To investigate the clinical features and in-hospital outcomes of young adults with acute myocardial infarction (AMI) in Singapore. METHODS:Between January 2005 to September 2010, 333 consecutive patients aged ≤ 45 years old were diagnosed to have AMI at our institution. As Singapore is a multi-ethnic society, we also analysed whether ethnic differences exist between the three dominant ethnic groups, Malay, Chinese and Indian with regards to the clinical features. Clinical data was collected retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 19 publications
7
33
2
Order By: Relevance
“…These findings are inconcordance with most of the recent studies. 7,14,15 In our study, the most common complication in young STEMI patients was arrhythmias (5.3%) followed by cardiogenic shock (4.5%) and heart failure, 3,6 which was similar to the study by Wong et al, 12 in which the most common complication was arrhythmias (7.2%) followed by cardiogenic shock (4.5%).…”
Section: -10% Of Myocardial Infarctions (Mi) Occur In Patients Youngersupporting
confidence: 78%
See 1 more Smart Citation
“…These findings are inconcordance with most of the recent studies. 7,14,15 In our study, the most common complication in young STEMI patients was arrhythmias (5.3%) followed by cardiogenic shock (4.5%) and heart failure, 3,6 which was similar to the study by Wong et al, 12 in which the most common complication was arrhythmias (7.2%) followed by cardiogenic shock (4.5%).…”
Section: -10% Of Myocardial Infarctions (Mi) Occur In Patients Youngersupporting
confidence: 78%
“…7,8,9,10,11 In our study, mean age of presentation was 39.14 years, which was in similar range with that to some recent studies done in Asian population. As studies done by Wong et al, 12 and Al Khadra et al, 13 showed mean age of 39.9, and 40 years. Our study showed 6.8% of patients were younger than 30 years which were slightly higher than few recent This may be the sign of increasing trend of young patients developing CAD.…”
Section: -10% Of Myocardial Infarctions (Mi) Occur In Patients Youngersupporting
confidence: 48%
“…Acute myocardial infarction (AMI) refers to the drastically reduced or interrupted blood supply of the coronary arteries, leading to myocardial ischemia (Wong et al 2012). It is characterized by dull chest pain, arrhythmia, shock and heart failure (Boateng and Sanborn 2013).…”
Section: Introductionmentioning
confidence: 99%
“…6 Their mean age at presentation was 39.9±4.2 years in Indian population. In the overall study group, the mean age at presentation was 40.2±4.0 years (range 25 to 45 years) with a male predominance (94%).…”
mentioning
confidence: 97%
“…8 Pong C found in their study that the mean BMI was 26.1±3.8 kg/m 2 with 37% of young adults considered obese by Asian BMI criteria. 6 Cigarette smoking was identified as a major risk factor in 138 (46%) patients. The least common risk factor i.e.…”
mentioning
confidence: 99%